Clinical outcomes in octogenarians treated with docetaxel as first-line chemotherapy for castration-resistant prostate cancer. (February 2016) - Veccia, Antonello; Caffo, Orazio; De Giorgi, Ugo; Di Lorenzo, Giuseppe; Ortega, Cinzia; Scognamiglio, Florinda; Aieta, Michele; Facchini, Gaetano; Mansueto, Giovanni; Mattioli, Rodolfo; Procopio, Giuseppe; Zagonel, Vittorina; et al.
Aim: To assess clinical outcomes in octogenarians treated with docetaxel (DOC) for metastatic castration-resistant prostate cancer.Patients & methods: The multicenter retrospective study was based on a review of the pre- and post-DOC clinical history, DOC treatment and outcomes.Results: We reviewed the records of 123 patients (median age: 82 years) who received DOC every 3 weeks or weekly, without significant grade 3–4 toxicities. Median progression-free survival was 7 months; median overall survival from the start of DOC was 20 months, but post-progression treatments significantly prolonged overall survival.Conclusion: The findings of this study suggest that toxicity is acceptable, survival is independent of patient's age and survival can be significantly prolonged by the use of new agents.